OFR-105(2)-84 Ground And Air Vibrations Caused By Surface Blasting. Volume 2 Ground Vibration Monitoring And Assessment Of Conventional Predictors - Sally A. Shoop (The National Institute for Occupational Safety and Health (NIOSH), 1983)
Thirty-seven blasts have been monitored using either three or four seismographs, at four coal strip mines and at a limestone quarry. Statistical analysis of the data shows that square-root, cube-root, and site-specific scaling methods predict peak particle velocities with about the same (low) degree of reliability. Some mines have peak particle velocities that are significantly lower or higher than the U.S. Bureau of Mines averages (Siskind et al., 1980). This suggests that the option provided by the proposed regulations (Office of Surface Mining, 1983), to adjust blast designs based on site-specific measurements could be highly beneficial both to operators and to the public. The frequency spectra reveal that the predominant frequencies were generally less than 50 Hz but several blasts had a significant amount of energy up to 125 Hz. In some cases the vibration energy was concentrated at frequencies corresponding to the delay intervals.